Generalization of Slightly Compressible Modules - Samruam Baupradist; Phatsarapa Janmuang; Suphawat Asawasamrit (Journal of Mathematical and Fundamental Sciences, 2018)
In this paper, we give a generalization of slightly compressible modules. We introduce the notion of M-slightly compressible modules, i.e. a right R module N is called M-slightly compressible if for every nonzero submodule A of N there exists a nonzero R-homomorphism s from M to N such that . Many examples of M-slightly compressible modules are provided. Some results on M-slightly compressible modules are obtained, which are interesting and important.